El Internet, el Big Data y el tratamiento de datos personales - Mubarak Aguad, Laisha (2020)
The internet and social networks have revolutionized our lives, generating a greater dependence on social endeavors, generating a greater concern regarding cyber security and the proper treatment of personal data on the web, since that the misuse of this information could affect our personal privacy. However, in most cases, the privacy and personal data protection policies offered to users are unilateral and difficult to understand, and therefore are rarely read. On that account, the author will raise the new challenges for the application of the regulations to these technologies.